Associate Professor Dr. Mohd. Ridzuan Darun appointed as UMP new Registrar - UMP, PNC (2019)
Associate Professor Dr. Mohd Ridzuan Darun has been appointed as the new Registrar and Chief Operating Officer (COO) for Universiti Malaysia Pahang (UMP) for two years effective March 15, 2019.